Házásságöt Kötöttek Herboly . Ildikó . És . Kocsár . Miklós 1961 . Oktober . 28 Án. - Stettner, Bela (1928-1984) (1961)
Młoda para wzdłuż krawędzi napis: Házásságöt Kötöttek Herboly . Ildikó . És . Kocsár . Miklós 1961 . Oktober . 28 Án.